Adverse childhood experiences influence development of pain during pregnancy. (3rd June 2015) - Drevin, Jennifer; Stern, Jenny; Annerbäck, Eva‐Maria; Peterson, Magnus; Butler, Stephen; Tydén, Tanja; Berglund, Anna; Larsson, Margareta; Kristiansson, Per
Abstract Objective To investigate the association between adverse childhood experiences (ACE) and pain with onset during pregnancy. Design Cross‐sectional study. Setting Eighteen antenatal clinics in southern Mid‐Sweden. Sample Of 293 women invited to participate, 232 (79%) women agreed to participate in early pregnancy and were assessed in late pregnancy. Methods Questionnaires were distributed in early and late pregnancy. The questionnaires sought information on socio‐demography, ACE, pain location by pain drawing and pain intensity by visual analogue scales. Distribution of pain was coded in 41 predetermined areas. Main outcome measures Pain in third trimester with onset during present pregnancy: intensity, location and number of pain locations. Results In late pregnancy, 62% of the women reported any ACE and 72% reported any pain location with onset during the present pregnancy. Among women reporting any ACE the median pain intensity was higher compared with women without such an experience (p = 0.01). The accumulated ACE displayed a positive association with the number of reported pain locations in late pregnancy (rs = 0.19, p = 0.02). This association remained significant after adjusting for background factors in multiple regression analysis (p = 0.01). When ACE was dichotomized the prevalence of pain did not differ between women with and without ACE. The subgroup of women reporting physical abuse as a child reported a higher prevalence of sacral and pelvic pain (p = 0.0003 and p = 0.02, respectively). Conclusions Adverse childhood experiences were associated with higher pain intensities and larger pain distributions in late pregnancy, which are risk factors for transition to chronic pain postpartum.